PENGEMBANGAN E-LKPD MUATAN HOTS BERBASIS QUIZIZ MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI - wistiawati lasoma; Andi Nurwati S.S; Zohrawaty Hiola (LPPM IAD Probolinggo, 2026)
This study aims to develop Quizizz-based E-LKPD containing Higher Order Thinking Skills (HOTS) on the material of Plants as Sources of Life on Earth for fourth-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The instruments used are validation sheets from material experts, media experts, and student response questionnaires. The results of the study show that the developed E-LKPD obtained the category of Feasibility of Quizizz-Based Student Worksheets on the Material of Plants as Sources of Life on Earth for Grade IV at SD Negeri 21 Limboto in the category of